2016
DOI: 10.1016/j.ajpath.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Altered Mitochondrial DNA Methylation Pattern in Alzheimer Disease–Related Pathology and in Parkinson Disease

Abstract: Mitochondrial dysfunction is linked with the etiopathogenesis of Alzheimer disease and Parkinson disease. Mitochondria are intracellular organelles essential for cell viability and are characterized by the presence of the mitochondrial (mt)DNA. DNA methylation is a well-known epigenetic mechanism that regulates nuclear gene transcription. However, mtDNA methylation is not the subject of the same research attention. The present study shows the presence of mitochondrial 5-methylcytosine in CpG and non-CpG sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
148
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 65 publications
5
148
1
5
Order By: Relevance
“…Blanch et al,. reported loss of mitochondrial DNA 5-methylation levels in the substantia nigra of PD patients [4]. These finding could support the hypothesis that mitochondrial dysfunction is a common molecular mechanism in PD pathogenesis.…”
Section: Epigenetics and The Genome: Dna Methylationsupporting
confidence: 55%
See 2 more Smart Citations
“…Blanch et al,. reported loss of mitochondrial DNA 5-methylation levels in the substantia nigra of PD patients [4]. These finding could support the hypothesis that mitochondrial dysfunction is a common molecular mechanism in PD pathogenesis.…”
Section: Epigenetics and The Genome: Dna Methylationsupporting
confidence: 55%
“…Additionally, a recent study showed that PD patients (n = 10) have a loss of m 5 C levels in the displacement loop (D-loop) of the substantia nigra mitochondrial DNA when compared with controls (n = 10) [4]. This could be attributable to dopaminergic neuronal loss in the substantia nigra, but methylation levels of mitochondrial NADH dehydrogenase 6 ( ND6 ) in this region were similar between PD patients and controls suggesting that the m 5 C methylation changes in the mitochondrial D-loop are not due to neuronal loss [4].…”
Section: Epigenetics and The Genome: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study aims to gain insight into functional effects of mtDNA methylation, if present at all. We hypothesize that differential mtDNA cytosine methylation affects mtDNA gene expression or mtDNA replication, and as such may contribute to the pathogenesis of various diseases 14, 1619 . Here, we show that low levels of methylation can be detected in the mtDNA of various cancer cell lines and fibroblasts of a mtDNA disease patient.…”
Section: Introductionmentioning
confidence: 99%
“…However, most research is either focussed on low resolution, global DNA methylation, or candidate gene DNA methylation changes using techniques such as bisulfite pyrosequencing [20]. These recent publications have indicated that differences in mtDNA methylation are present in a variety of different phenotypes [2429] and may have potential utility as a biomarker [30]. In addition, a recent study has explored the use of Methylated DNA Immunoprecipitation Sequencing (MeDIP-seq) to investigate changes in mtDNA methylation across 39 cell lines and tissues from publicly available data [31].…”
Section: Introductionmentioning
confidence: 99%